Atmospheric composition and climate on the early Earth - Kasting, James F (The Royal Society, 2006)
Oxygen isotope data from ancient sedimentary rocks appear to suggest that the early Earth was significantly warmer than today, with estimates of surface temperatures between 45 and 85°C. We argue, following others, that this interpretation is incorrect—the same data can be explained via a change in isotopic composition of seawater with time. These changes in the isotopic composition could result from an increase in mean depth of the mid-ocean ridges caused by a decrease in geothermal heat flow with time. All this implies that the early Earth was warm, not hot. A more temperate early Earth is also easier to reconcile with the long-term glacial record. However, what triggered these early glaciations is still under debate. The Paleoproterozoic glaciations at approximately 2.4 Ga were probably caused by the rise of atmospheric O(2) and a concomitant decrease in greenhouse warming by CH(4). Glaciation might have occurred in the Mid-Archaean as well, at approximately 2.9 Ga, perhaps as a consequence of anti-greenhouse cooling by hydrocarbon haze. Both glaciations are linked to decreases in the magnitude of mass-independent sulphur isotope fractionation in ancient rocks. Studying both the oxygen and sulphur isotopic records has thus proved useful in probing the composition of the early atmosphere.